The Competency of Changing the Deed Legal Framing in Case of Case Declination by the Competent Body. Resumption and Repetition of the on-site Investigation - Palcu, Pavel; Moroșteș, Anca Florina (Journal of Legal Studies, 2022)
The criminal cases solved lately by the Prosecutor’s office by the court and by the local prosecutor’s offices brought under discussion and caused various opinions on the competency of changing the legal framework of the deed by hitting or other violent acts to attempted murder provided the competency being declined by the prosecutor’s offices by the district courts to the prosecutor’s office by the county court. This issue has become particularly important in view of the recent finding by the Constitutional Court that the elimination from absolute nullities of non-compliance with the rules of substantive jurisdiction and according to the quality of the person of the criminal prosecution bodies is unconstitutional [1]. There are also different points of view regarding the resumption and repetition of the on-site investigation, the conditions in which they intervene, who continues to carry it out, but also the way in which their forensic fixation is fixed.